Marketing Strategy For 3M Personal Protective Equipment At Coal Mining In East Kalimantan - Dipowicaksono, Fiqi; Wibowo, Satya Aditya (The Indonesian Journal of Business Administration, 2013)
The use of Personal Protective Equipment (PPE) in the coal mining industry is very important. Beside its use is required by the government to succeed the Health and Safety Environment (HSE) program, as it is known that the potential dangers of coal mining jobs are very large. A large number of coal mines in East Kalimantan, and the requirement of PPE product by the coal mining companies, there is a business opportunity for the company, which sell PPE product to market its product. PT. 3M Indonesia, which has been operating in Indonesia since 1975, has a mining division to offer PPE products under Security Protection System (SSPS) business unit. Currently, the mining division of PT. 3M Indonesia is wanted to increase the revenue from the sale of its PPE products. The number of coal miners in East Kalimantan has reached 63.538 (Dinas Pertambangan Prov. Kalimantan Timur) workers, while the total number of coal miners in East Kalimantan who already using 3M Indonesia’s PPE product are around 17.700 workers (source: PT. 3M Indonesia). These opportunities can be exploited by PT. 3M Indonesia to penetrate the PPE product sales to coal mining companies that have not use 3M Indonesia’s PPE products yet. To penetrate PPE sales to mining companies in East Kalimantan, the root cause of the business problem is need to be determined. It required an in-depth analysis of the internal sector, external sector, and the company's business growth strategy. Internal analysis conducted by analyzing Segmenting, Targeting and Positioning, Marketing Mix (4Ps) of PT. 3M Indonesia’s PPE product. While the external analysis is done by analyzing Porter's Five Forces analysis, PEST analysis, and customer analysis. Ansoff market/product expansion grid and strategic direction options are used to analyze the company growth strategy. Interviews with customers were also conducted to strengthen all analysis. Based on the analysis and interviews conducted, the root cause of the business is from the internal side of the company, the positioning statement of PPE products, distribution side, and promotion activities. The purpose of this final project is to provide solutions and recommendations as well as the stages of implementation of marketing strategies for PT. 3M Indonesia to then be able to increase the PPE products sales. The solutions proposed to PT. 3M Indonesia are to, manage its sales force, improve the distribution channels, conducting several promotional activities, and maintain customer relationship by creating customer intimacy. Keywords: Personal Protective Equipment, East Kalimantan Coal Mine, Health and Safety Environment, customer intimacy, customer relationship.